Physiological responses to rock climbing in young climbers. Issue 12 (23rd November 2007) - Morrison, Audry Birute; Schöffl, Volker Rainer
Abstract : Key questions regarding the training and physiological qualities required to produce an elite rock climber remain inadequately defined. Little research has been done on young climbers. The aim of this paper was to review literature on climbing alongside relevant literature characterising physiological adaptations in young athletes. Evidence-based recommendations were sought to inform the training of young climbers. Of 200 studies on climbing, 50 were selected as being appropriate to this review, and were interpreted alongside physiological studies highlighting specific common development growth variables in young climbers. Based on injury data, climbers younger than 16 years should not participate in international bouldering competitions and intensive finger strength training is not recommended. The majority of climbing foot injuries result from wearing too small or unnaturally shaped climbing shoes. Isometric and explosive strength improvements are strongly associated with the latter stages of sexual maturation and specific ontogenetic development, while improvement in motor abilities declines. Somatotyping that might identify common physical attributes in elite climbers of any age is incomplete. Accomplished adolescent climbers can now climb identical grades and compete against elite adult climbers aged up to and >40 years. High-intensity sports training requiring leanness in a youngster can result in altered and delayed pubertal and skeletal development, metabolic and neuroendocrine aberrations and trigger eating disorders. This should be sensitively and regularly monitored. Training should reflect efficacious exercises for a given sex and biological age.